The Paschal feast in the Bible - Grelot, Pierre, 1917- (The Living word series ;, 1966)
The purpose of this book is to open the eyes of Christians to the whole paschal scene, to the full mystery of our redemption which reaches back to the beginnings of the history of Israel. We learn how our own feast of Easter is actual a multiple feast, embracing the ancient celebrations of the deliverance, the unleavened bread, and the paschal lamb. The history of the Old Testament is the history of the people of God. It is our history.